Restricted Water Intake Adversely Affects Rat Vocal Fold Biology. (13th July 2020) - Duan, Chenwei; do Nascimento, Naila Cannes; Calve, Sarah; Cox, Abigail; Sivasankar, M. Preeti
Abstract : Objectives: A holistic understanding of the many ways that systemic dehydration affects vocal fold biology is still evolving. There are also myriad physiologically relevant methodologies to induce systemic dehydration. To untangle the effects of systemic dehydration on vocal fold biology, we need to utilize realistic, clinically translatable paradigms of systemic dehydration in lab animals. Restricted access to water accommodates clinical translation. We investigated whether systemic dehydration via reduced water intake would negatively affect vocal fold biology. Study Design: Prospective, in vivo study design. Methods: Male Sprague Dawley rats (N = 13) were provided 4 mL/100 g of water/day for 5 days, whereas male control rats (N = 8) were given ad lib access to water. Following euthanasia, tissues were processed for histological staining, gene expression, and protein assays. Results: Renin gene expression level in kidneys increased significantly ( P ≤ .05), validating dehydration. Dehydration induced by restricted water access downregulated the gene expression of interleukin‐1α and desmoglein‐1 ( P ≤ .05). Hyaluronidase‐2 gene expression increased after dehydration ( P ≤ .05). The protein level of desmoglein‐1 decreased after dehydration ( P ≤ .05). Histological analyses suggested decreased hyaluronan ( P ≤ .05) in the water‐restricted rat vocal fold. Conclusion: Reduced daily water intake for just 5 days impairs vocal fold biology by disrupting inflammatory cytokine release, reducing plasma membrane integrity, and disrupting the hyaluronan network. This is the first study investigating the dehydrating effects of restricted water intake on vocal fold tissue in an in vivo model. Level of Evidence: NA (prospective animal study). Laryngoscope, 131:839–845, 2021